Perceptions of Live Donor Kidney Transplantation Using Segmentation Analysis and Perceptual Mapping to Understand Differences by Self-Reported Health Status in People on Dialysis - Bass, Sarah Bauerle; Hollin, Ilene L.; Kelly, Patrick J.; Alhajji, Mohammed; D’Avanzo, Paul; Maurer, Laurie; Gillespie, Avrum; Schatell, Dori; Gardiner, Heather (Frontiers in Communication, 2022)
Living donor kidney transplantation is a superior treatment option for those with end stage kidney disease, but most transplants are from deceased donors. Securing a living donor for living donor kidney transplantation requires effective, well-timed communication which many may find difficult or intimidating. This study uses segmentation analysis and an innovative marketing technique called perceptual mapping to create three dimensional models to compare living donor kidney transplant perceptions by self-reported health status in 160 end-stage kidney disease dialysis patients of two hospital-based dialysis units and an online forum through cross-sectional surveys. Findings indicate patients with poor self-reported health status are more concerned with not knowing what to say or being afraid a person would say no to living donor kidney transplantation. They are also concerned about the donor’s ability to care for family or donate in the future. They are, however, more likely to see benefits of living donor kidney transplantation, including the kidney lasting longer and having a greater quality of life. Findings reveal messages that could be emphasized in interventions to enhance the ability to ask for living donor kidney transplantation, especially in those assessed as having poor health status. Segmentation analysis and perceptual mapping methods can provide a more nuanced look at how best to develop intervention content to increase living donor kidney transplant.